The Spanish Monarchy and the Creation of the Viceroyalty of New Granada (1717-1739): The Politics of Early Bourbon Reform in Spain and Spanish America - Eissa-Barroso, Francisco A (Early American History Series, 2016)
In The Spanish Monarchy and the Creation of the Viceroyalty of New Granada (1717-1739), Francisco A. Eissa-Barroso analyzes the politics behind the most salient Bourbon reform introduced in Spanish America during the early eighteenth century. Readership: Scholars and students of colonial Spanish America, the Spanish Atlantic, and early modern Spain interested in both empire and colonialism and, furthermore, the development and administration of early modern, fiscal military states.